Suriname : Southeast Asian loggers' latest object of desire. - TSURUOKA, Doug (1995)
Notes that Southeast Asian logging companies are moving into Suriname, the most densely forested country in the world, to obtain fresh supplies of choice hardwoods. The country's lax forestry regulations put the rainforest - and the indigenous groups that live in it - at risk.